CT KUB evaluation of suspected urolithiasis - Jaiswal, Pooja; Shrestha, Shreejana; Dwa, Yogita; Maharjan, Dinesh; Sherpa, Ngawang Temba (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Non-contrasted computed tomography scan for kidney, ureter, and bladder (CT KUB) for diagnosis of urolithiasis is important for accurate diagnosis, followup, and management. Unlike USG, CT KUB has more diagnostic yield in urolithiasis and other incidental findings. This study aims to evaluate the use of the CT KUB in suspected urolithiasis, presented with severe flank pain.Method: A retrospective observational study was carried out in the Department of Radiology and Imaging, Patan Hospital, Nepal.TheCT KUB reports of patients with suspected urolithiasis from a period of 3 years from Jan 2017 to Jan 2020 were analyzed for evidence of urolithiasis and secondary signs of obstruction as ‘diagnostic’ of CT KUB. Other incidental radiological findings were further analysed and categorized into urinary and extra-urinary. Ethical approval was obtained.Association of USG and CT KUBwas analysed using Chi-square test,with  p value